Reduced sensitivity of lager brewing yeast to premature yeast flocculation via adaptive evolution. (September 2022) - He, Yang; Yin, Hua; Dong, Jianjun; Yu, Junhong; Zhang, Lei; Yan, Peng; Wan, Xiujuan; Hou, Xiaoping; Zhao, Yuxiang; Chen, Rong; Gibson, Brian; Krogerus, Kristoffer
Abstract: Malt-induced premature yeast flocculation (PYF) is a sporadic problem within the brewing industry. The use of PYF malts is concomitant with a number of negative impacts on beer quality, including incomplete fermentation and/or flavor defects. Although malt-induced PYF is widely acknowledged, actions taken so far have proved insufficient to solve the PYF-related issues. To limit the detrimental effects of PYF malts on beer production, an adaptive laboratory evolution (ALE) process was applied in this study to an industrial lager brewing yeast strain (TT02), in an attempt to generate variant strains with improved fermentation performance in PYF wort. Through a batch fermentation-based adaptation process, evolved variants were isolated and screened for their phenotypic and metabolic traits. The investigation focused mainly on the tendency to remain in suspension, fermentation capacity and final acetaldehyde concentration. We successfully obtained a variant (TT02-30 T) with improved fermentation properties. The improvement was seen in worts prepared from different types of PYF malt as well as normal malt. Furthermore, ALE of lager brewing yeast in PYF wort yielded a wide array of mutations. Several changes in the genomes (copy number variation in flocculin encoding gene FLO1 and a missense SNP in a putative mitochondrial membrane protein coding gene FMP10 ) of the variant strains relative to the original strain were observed. These could potentially contribute to the improved yeast suspension during fermentation. Importantly, mutational enrichment in genes related to ion binding in PYF-evolved strains suggests the involvement of the yeast ion transportation process in dealing with the PYF stress. Our study demonstrates the possibility of attenuating yeast sensitivity to PYF malts over time through adaptive laboratory evolution via spontaneous mutation. Highlights: Adaptive laboratory evolution shows the possibility of attenuating yeast sensitivity to PYF. The evolved variants are capable of improving beer quality with PYF malts. Lager yeast adapt to PYF environment through a combination of genetic mutations.